COMPARISON BETWEEN CRAZY RICH ASIAN NOVEL BY KEVIN KWAN AND CRAZY RICH ASIAN MOVIE - Fitriana, Tyas; Surya, Satyawati; Muhajir, Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
Recently, there have been many movies that are made based on novels. Crazy Rich Asian is one of the movies based on a novel because the novel came first, then that was made into the movie. The purposes of this research are to find out the similarities and differences of the intrinsic elements in the movie and the novel and reveal the plot changes. This research used Robert Stanton’s theory to describe the intrinsic elements that cover facts, themes, and literary devices. Meanwhile, the ecranisation theory by Pamusuk Eneste is employed to reveal the plot changes, thus including additions, reductions, and changes of both works. The data sources come from novels and movies, shown by quotes, narration, dialogue, and scenes. The results found in this research between the novel’s plot and movies show twenty-six differences in intrinsic elements of both works. After that, seven additions, five reductions, and six changes or modifications occurred in the story’s plot. In conclusion, this research implies that differences, similarities, and changes can occur when a novel is made into a movie.